2022
DOI: 10.1155/2022/3151090
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Progression Mechanism and Key Genes in Early Stage of mTBI

Abstract: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease caused by repetitive mild traumatic brain injury (rmTBI), and the lack of sensitive diagnostic and prognostic biomarkers for rmTBI leads to long-term sequelae after injury. The purpose of this study is to identify key genes of rmTBI and find the potential progression mechanism in early stage of mTBI. We downloaded the gene expression profiles of GSE2871 from Gene Expression Omnibus (GEO) datasets. Differentially expressed genes (DEGs) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%